Strain Hardening Behavior of Laminate Structure With Stable bcc/fcc Bimetal Interfaces - Huang, Xuqiang; Lu, Zhaoyang; Cai, Minghui; Hodgson, Peter D. (Frontiers in Materials, 2020)
This work developed a well-bonded bcc/fcc bimetal interphase, which was produced by a two-step process involving diffusion bonding and conventional rolling. The high-quality interface maintained its integrity even at fracture. The earlier tensile instability in the core steel layer was constrained by the neighbouring stable Cu layers on both sides, leading to extra strain hardening and consequently higher ductility. An increase in twin density or slip bands and shear deformation between the layers might be the primary causes for the observed hardening behaviours in the near-interface regions.